Physical controls on sand composition and relative durability of detrital minerals during ultra‐long distance littoral and aeolian transport (Namibia and southern Angola). Issue 4 (26th January 2015) - Garzanti, Eduardo; Resentini, Alberto; Andò, Sergio; Vezzoli, Giovanni; Pereira, Alcides; Vermeesch, Pieter; Lancaster, Nick
Abstract Sediment in coastal Namibia to southern Angola is supplied dominantly from the Orange River with minor additional fluvial input and negligible modifications by chemical processes, which makes this a great test case for investigating physical controls on sand texture and composition. This study monitored textural, mineralogical and geochemical variability in beach and aeolian‐dune sands along a ca 1750 km stretch of the Atlantic coast of southern Africa by using an integrated set of techniques, including image analysis, laser granulometry, optical microscopy, Raman spectroscopy and bulk‐sediment geochemistry. These results contrast with previous reports that feldspars and volcanic detritus break down during transport, that sand grains are rounded rapidly in shallow‐marine environments, and that quartzose sands may be produced by physical processes. Mechanical wear is unable to modify the relative abundance of detrital components, including pyroxene and mafic volcanic rock fragments traditionally believed to be destroyed rapidly. The sole exceptions are poorly lithified or cleaved sedimentary/metasedimentary rock fragments, readily lost at the transition to the marine environment, and slow‐settling flaky micas, winnowed and deposited offshore. Coastal sediments tend to be depleted in relatively mobile amphibole, preferentially entrained offshore or re‐deposited in sheltered beaches, while less mobile garnet is retained onshore. No detrital mineral displays a significant increase in grain roundness after 300 to 350 km of longshore transport in high‐energy littoral environments from the Orange mouth to south of the Namib Erg, but all minerals get rapidly rounded after passing into the dunefield. Pyroxene and opaques get rounded faster than harder quartz and garnet, but sand mineralogy remains unchanged. Excepting strong transient selective‐entrainment effects, physical processes are unable to modify sand composition significantly. Selective mechanical breakdown can be largely neglected in quantitative provenance analysis of sand and sandstone even in the case of ultra‐long‐distance transport in high‐energy environments dominated by strong persistent winds and waves.